Control of Intra-Thymic αβ T Cell Selection and Maturation by H3K27 Methylation and Demethylation - Bosselut, Rémy (Frontiers in Immunology, 2019)
In addition to transcription factor binding, the dynamics of DNA modifications (methylation) and chromatin structure are essential contributors to the control of transcription in eukaryotes. Research in the past few years has emphasized the importance of histone H3 methylation at lysine 27 for lineage specific gene repression, demonstrated that deposition of this mark at specific genes is subject to differentiation-induced changes during development, and identified enzymatic activities, methyl transferases and demethylases, that control these changes. The present review discusses the importance of these mechanisms during intrathymic αβ T cell selection and late differentiation.